Management of Fibroadenoma in a 12-Year-Old Dachshund Mix Dog - Rahmatullah, Aldin Akbar; Putri, Cindy Ercha Aulia; Ratnaningtyas, Nurrohmah; Pratama, Syifa Ramadhan; Karim, Nuurin Ajrin; Akintunde, Adeyinka Oye (Universitas Airlangga, 2026)
Mammary tumors are a significant concern in canine veterinary medicine, with fibroadenoma being a rare benign subtype. This case report details the successful management of fibroadenoma in a 12-year-old, non-spayed, female Dachshund mix presenting with multiple abdominal masses (3–6 cm in diameter). Clinical examination showed stable vital signs (body temperature 38.5°C, pulse 110 bpm, respiratory rate 30 breaths/min). Diagnostic workup included ultrasonography, hematology, and histopathology, confirming fibroadenoma characterized by adenoma clusters within dense connective tissue. The term